Does less invasive surfactant administration during high-flow nasal cannula oxygen treatment reduce the need for invasive ventilation in late preterm and early term born infants with respiratory distress? A study protocol for a single-centre study with a treatment and control arm - Anne Greenough; Theodore Dassios; Eleanor Jeffreys; Chris Harris; Allan Jenkinson; Ravindra Bhat; Ourania Kaltsogianni (BMJ Open)
Introduction Up to 40% of late preterm and early term infants require neonatal admission with respiratory disease being the most common cause. Less invasive surfactant administration (LISA) has previously been used with good success in the very preterm population, but it is unclear whether late preterm infants suffering from respiratory distress syndrome and early term infants suffering from secondary surfactant deficiency might also benefit from LISA. Continuous positive airway pressure (CPAP) in that population can increase asynchrony and air leaks, whereas these may be avoided by using high flow nasal cannula (HFNC). This trial will investigate whether LISA during HFNC reduces the need for invasive ventilation.Methods and analysis This non-blinded, single-centre study with a treatment and a control arm will take place on the Neonatal Intensive Care Unit at King’s College Hospital National Health Service (NHS) Foundation Trust and the local neonatal unit at the Princess Royal University Hospital. The study will recruit 245 infants born between 34+0 and 38+6 weeks gestational age, who are requiring respiratory support via HFNC. The 245 participants will be placed into a control and treatment group. Those infants eligible for SURFactant Or Not (SurfON) will be randomised as per the SurfON protocol. The remaining infants will, where possible, be recruited to the treatment group. All recruited infants will have 2 minutes of respiratory function monitoring. Those receiving LISA will receive a further 2 minutes of monitoring after the procedure. As HFNC, LISA and respiratory monitoring are part of routine clinical practice, retrospective consent will be gained from parents or guardians after the procedure to analyse the respiratory function data. The primary outcome will be the percentage of neonates needing invasive ventilation within 72 hours from birth. The secondary outcomes are length of neonatal unit stay; the cost of stay as estimated via standard NHS tariffs; and the lung function parameters including tidal volume, respiratory rate, end tidal CO2 (ET CO2), fraction of inspired oxygen (FiO2) and ratio of oxygen saturations to fraction of inspired oxygen (SpO2/ FiO2) ratio before and 2 minutes after LISA and the SpO2/FiO2 ratio 2 hours after the administration of LISA.Ethics and dissemination A favourable opinion was sought and obtained from the London – Hampstead Research Ethics Committee and Health Research Authority for the study protocol and other relevant documentation (informed consent forms and patient information leaflets) prior to commencing the study (REC reference: 24/PR/0431). Anonymised study data will be presented at conferences and published by the investigators in peer-reviewed journalsTrial registration number NCT06421506.